Pathological variations in mummified feet between two near-distance/long-time populations in Ancient Egypt. Issue 1 (December 2015) - Isidro, Albert; Huber, Beatrice; Malik, Aamer; Malgosa, Assumpció
Abstract Background In ancient populations, a significant quantity of foot pathology was related either to the type of footwear they used or the underlying terrain they walked on. Our study was carried out to analyze these parameters with the foot pathologies the mummies presented. Methods Between 2006 and 2012, more than 650 individuals were recovered from the Sharuna and Qarara necropolis (Middle Egypt) dating from the VIth Dynasty of the first Ptolemaic Period to the second Coptic Period. From among them, a total of 73 mummified feet (41 from Sharuna and 32 from Qarara) were studied. We took into account the differences existing between both sites in location (15 km apart) and in time (2500 years apart). Results Almost all feet from Sharuna were wrapped and impregnated with a preservative substance (anthropological mummification), while the mummification process in Qarara was quite natural. Pathologies were found in 36 of the 73 ft (20 from Sharuna and 16 from Qarara). The differences in foot pathologies between the two sites were analysed. Conclusions The foot pathologies we found in both necropolises have led us to hypothesise that the majority of the diachronic differences could be related more to progressive changes in the type of the terrain brought out through droughts, than the changes in footwear habits.